Peningkatan Branding pada UMKM Tria Production Melalui Petunjuk Arah, Logo Produk (Catering, Cake dan Dekorasi) dan Update Sosial Media : Desa Tireman - Desfitasari Berliana Anggraeni Trissinta; Elsa Putri Aulia; Moch Johan Ariyanto; Dian Ayu Liana Dewi (BADAN PENERBIT STIEPARI PRESS, 2025)
Business Work Lecture (KKU) is a form of community service activity carried out by students with the aim of applying the knowledge gained during lectures to the real world, especially in the business and industrial sectors. This activity not only provides practical experience, but also equips students with additional skills, such as managerial, communication, and problem-solving skills, so that they are better prepared to face the professional world of work. One of the partners in the implementation of KKU YPPI Rembang University is the UMKM Tria Production, which operates in the fields of cakes, catering, and decoration. This UMKM is located in Tireman Village RT 1 RW 2, Rembang District, Rembang Regency. Tria Production has great potential to grow because its culinary products and decoration services are quite attractive and have broad market opportunities. However, this UMKM still faces several obstacles, especially in terms of branding which causes this business to be less well-known among the wider community, both around Rembang and outside the area. The identified problems included: (1) lack of proper financial management, resulting in unstructured financial records and reports; (2) limited social media promotion, resulting in suboptimal market reach; and (3) unattractive logo designs for cakes, catering, and decorations that did not optimally represent the business's identity. Through the month-long KKU program, students sought to provide concrete solutions. The program yielded several outputs: (1) a standing banner to clarify the business's location and make it more easily recognizable to the public; (2) the creation of a new logo as a more attractive and memorable brand identity; and (3) a promotional banner to expand information about the products and services offered. Therefore, the KKU program is expected to enhance the branding of the Tria Production MSME, making it better known to the public and enhancing its competitiveness.